2019
DOI: 10.51983/ajcst-2019.8.s3.2075
|View full text |Cite
|
Sign up to set email alerts
|

Acknowledgement Based Technique for Detection of the Wormhole Attack in RPL Based Internet of Things Networks

Abstract: Internet of Things (IoT) is the advanced technology, were the constrained nodes/things (all the objects around us such as chair, home, car, keys, etc.) will be connected to the internet to form a network, for sharing and monitoring the data, remotely. RPL (IPv6 Routing Protocol for Low Power and Lossy networks) is a routing protocol particularly designed for the constrained (low powered, low computation, less size, etc.) networks with the protocol 6LoWPAN (IPv6 Low Powered wireless Personal Area Networks). Due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Machine Learning Based Technique for Detection of Rank Attack in RPL based Internet of Things [41] and many others. Despite all existing protocols put in place, it was observed that limitations and drawbacks still exist as it was pointed out that many literatures only classified the security threat of IOT but could not suggest a total solution [17].…”
Section: Introductionmentioning
confidence: 99%
“…Machine Learning Based Technique for Detection of Rank Attack in RPL based Internet of Things [41] and many others. Despite all existing protocols put in place, it was observed that limitations and drawbacks still exist as it was pointed out that many literatures only classified the security threat of IOT but could not suggest a total solution [17].…”
Section: Introductionmentioning
confidence: 99%